Parental Bonding Instrument’s (pbi) psychometric properties of population from Medellín, Colombia - Gómez Maquet, Yvonne; Vallejo Zapata, Victor Julián; Villada Zapata, Johny; Zambrano Cruz, Renato (Pensando Psicología, 2010)
This paper is a product of the research “Parental Bonding Instrument (pbi) test’s standardization in college population from Medellín, Colombia”. This study purpose involved establishing the psychometric properties of pbi, developed in 1979 by Parker, Tupling and Brown as an objective test that pretends to measure and determine child-to-parent bonding. It is a retrospective test and it measures the assessed individual’s own perception about his/her relationship up to age 16 with his or her father and mother, separately. It consists of 25 items which evaluate two scales called for this study afecto and control, (care and overprotection, within the original). The study was conducted on a sample of 430 students from several colleges within Medellin and its metropolitan area, and reported a Cronbach’s alpha at 0,89 for paternal-care scale; 0,88 for maternal-care scale; 0,80 for paternal-overprotection scale and 0,85 for maternal-overprotection scale.